L’industrie des services sida : la construction des « victimes », des « volontaires » et des « experts » [1990] - Cindy Patton (Genre, Sexualité et Société)
Cindy Patton describes the ways in which the various populations most affected by the AIDS crisis in the beginning of the 1980’s in the United States have been classified according to previous homophobic and racist sets of representations. She also analyses how AIDS prevention and the provision of service to people living with AIDS have taken different paths and forms depending on the communities at stake. Gay communities have developed forms of service organization and responses to the epidemic based on expertise, thus receiving recognition and support from the general public as well as government agencies, while Haitian populations developed a more multi-service integrated approach, less recognized and therefore less funded. The author also describes how volunteer work, intrinsically linked to the State’s disengagement from public health, is structured in terms of gender, the labor division in the AIDS industry assigning the majority of women to positions of altruistic care-takers.